Public policy education in Thailand: from caged pedagogy to disciplinary Independence? - Theerapat Ungsuchaval (2022)
This study examines the state and development of public policy education in Thailand, including its dynamics over time, its institutional setting, and emerging forces acting upon it. It focuses on policy educational institutions, policy courses offered in universities, and national socio-political contexts that shape the academic profession. Policy education has heavily been developed and taught as a subset of public administration with predetermined specifications. However, it has potential to be an independent field. This study fills a notable research gap, as the topic has been largely neglected in international publications, especially works concerning the internationalization of policy education.